2016
DOI: 10.7567/apex.9.112301
|View full text |Cite
|
Sign up to set email alerts
|

Progression of rapid potential-induced degradation of n-type single-crystalline silicon photovoltaic modules

Abstract: This study addresses progression of potential-induced degradation (PID) of photovoltaic modules using n-type single-crystalline silicon cells. In a PID test in which a voltage of −1000 V was applied to the cells, the modules started to degrade within 10 s and the degradation saturated within 120 s, suggesting that PID is caused by positive charge accumulation in the front passivation films. We propose that these positive charges originate from positively charged K centers formed by extracting electrons from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(109 citation statements)
references
References 19 publications
6
102
1
Order By: Relevance
“…It has been reported that various kinds of PV cells, such as conventional p-type c-Si, [10][11][12][13][14] n-type front-emitter c-Si, [15][16][17][18][19] n-type rear-emitter c-Si, 19,20 n-type IBC c-Si, 22 a-Si thin-film, 24,25 CIGS thinfilm, [26][27][28] and CdTe thin-film 28,29 PV cells, undergo PID under negative bias. Herein, we first clarified how the J-V, EQE, and EL characteristics of SHJ PV modules change upon applying a negative bias.…”
Section: Degradation Behavior Of the Shj Pv Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that various kinds of PV cells, such as conventional p-type c-Si, [10][11][12][13][14] n-type front-emitter c-Si, [15][16][17][18][19] n-type rear-emitter c-Si, 19,20 n-type IBC c-Si, 22 a-Si thin-film, 24,25 CIGS thinfilm, [26][27][28] and CdTe thin-film 28,29 PV cells, undergo PID under negative bias. Herein, we first clarified how the J-V, EQE, and EL characteristics of SHJ PV modules change upon applying a negative bias.…”
Section: Degradation Behavior Of the Shj Pv Modulesmentioning
confidence: 99%
“…In one noteworthy case, the EQE was reduced by at least half at short wavelengths (see the line "−2000 V, 21 days" in Figure 2). It has been reported that PID in many types of PV modules including p-type c-Si, 10 n-type front-emitter c-Si, 15,16,19 and CIGS 27 modules can be recovered by applying the opposite bias to that used in the degradation tests. To investigate whether such a regeneration effect occurs for the PID in SHJ PV modules, we applied a positive bias of +1000 V to a degraded module.…”
Section: Degradation Behavior Of the Shj Pv Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,[24][25][26][27][28][29] The PID-p in n-type IBC solar cells occurs under positive potential conditions, 9,[30][31][32] whereas the PID-p in n-type solar cells with a front p + emitter is observed under negative potential conditions. 14,15,[24][25][26][27][28][29] Both can be explained by the surface recombination of minority carriers arising from the charge fixed on the silicon dangling bonds back-bonded with nitrogen, known as "K centers," in the SiN x ARC layer. 9,24,25 If the ARC of p-type c-Si solar cells is constructed by the SiN x stacked on SiO 2 layers, PID-p can occur even in the p-type c-Si solar cells by applying a high positive voltage.…”
Section: Introductionmentioning
confidence: 99%
“…If the encapsulant with a relatively low volume resistivity on the order of 10 14 Ω cm, such as ethylene-vinyl acetate (EVA), is used, leakage current flows from the Al frame to the PV cells accompanied by a drift of Na from the cover glass to the PV cell. Such Na drift by a high electric field and migration to the pn junction in the PV cells are one of the possible origins of PID for p-type crystalline Si PV modules, [4][5][6][7] although PID is merely a generic name for the degradation induced by the potential difference between the Al frame and the PV cells, and the degradation behavior and mechanism of PID are essentially different for different types of PV cells: for p-type crystalline Si, 1,2,7,8) possibly due to the migration of Na; for n-type crystalline Si, [9][10][11][12] possibly due to charge recombination; for Si heterojunction, 13,14) due to the reduction of transparent conductive oxide (TCO) layer; thin-film Si, 15) due to the delamination of the TCO layer, Cu(In,Ga)Se 2 , 16,17) CdTe, 18) and others. Such mechanisms are still controversial in spite of much effort using various kinds of tools and techniques devoted to clarifying the main origins of PID.…”
Section: Introductionmentioning
confidence: 99%